Sufism and Religious Practices in Modern Lifestyle - Suraiya IT.; Syamsul Rijal; Zaenuddin Hudi Prasojo (Religió: Jurnal Studi Agama-agama, 2019)
Along with scientific development and technological growth which have created a lot of convenience to mankind there have also raised a deep cynicism towards the religious and spiritual aspects of life. Value crisis of humanity marked by the crisis of spirituality increased. Many societies are facing deep crisis. This condition makes the world vulnerable to violence and conflicts. Therefore, modern world society has been challenged to to be more attentive than before to deal with religious and spiritual values. This paper asserts that religion continues to be an important since it combines both personal and public character. Social problems faced by the modern world society such as cultural diversity, environmental preservation, economic equity, and conflict resolution are theologically reflected within the teaching of Islam. Sufism as a form of Islamic spiritualities offers some applicable answers for this phenomenon. In addition, characteristic of Sufism (mysticism) is commonly well known in almost all religions. Sufism cherishes from the private sphere into a popular Islamic culture. This research would like to see how the phenomenon of spiritual movement in the dimension of Sufism has a real powerful to improve social problem of the modern world.